2011
DOI: 10.5888/pcd9.110091
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Awareness and Implementation of Food and Physical Activity Policies in Utah Elementary Schools, 2010

Abstract: Introduction Schools are a key venue for childhood obesity prevention policies. The objective of this study was to examine factors associated with elementary school teacher awareness and implementation of their schools' food and physical activity policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The system survey included 21-items on systemlevel support for LWP implementation, and this summary score (sum of ''fully implemented'') exhibited high internal consistency (α = .865). The summary score was normally distributed (skewness = 0.128), and examined as a continuous variable (M = 10.8, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Table 1 shows the item responses.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The system survey included 21-items on systemlevel support for LWP implementation, and this summary score (sum of ''fully implemented'') exhibited high internal consistency (α = .865). The summary score was normally distributed (skewness = 0.128), and examined as a continuous variable (M = 10.8, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Table 1 shows the item responses.…”
Section: Instrumentationmentioning
confidence: 99%
“…In response to this mandate, the majority of US school systems now have written LWPs in place . LWPs are only effective, however, if implemented . More recent legislation, the Healthy Hunger‐Free Kids Act (HHFKA) of 2010, expanded upon the LWP provision in the CNRA to focus more heavily on the implementation, evaluation, and reporting of LWPs in schools.…”
mentioning
confidence: 99%
“…For example, Lanier et al [101] found that teachers were often unaware of their respective school's wellness policies, and two studies identified the school principals' leadership as key to improved physical activity and nutrition policy implementation [102,103]. One study identified that lower complexity, higher compatibility, and greater perceived relative advantage assisted schools in implementing nutrition guidelines [104].…”
Section: Policy Issuesmentioning
confidence: 99%
“…Lack of knowledge regarding policies led to school staff's avoidance of implementing aspects of the referral system (e.g., not providing referrals or referral guides to students) for fear of being noncompliant with policies. As we saw in the Western site, even in a supportive sexual health environment, school staff who serve as gatekeepers (i.e., principals, office staff, hall monitors) were unaware of the policies of student access to services; this gap in awareness and knowledge has been corroborated in past studies as barriers to sexual health and nutrition education and policy implementation within schools [28][29][30][31]. Equally important to increasing staff's knowledge of stateand district-level sexual health policies is addressing negative attitudes and stigma.…”
Section: Discussionmentioning
confidence: 89%